Cobalt Bis(dicarbollide) Alkylsulfonamides: Potent and Highly Selective Inhibitors of Tumor Specific Carbonic Anhydrase IX. Issue 3 (21st September 2020) - Grüner, Bohumír; Kugler, Michael; El Anwar, Suzan; Holub, Josef; Nekvinda, Jan; Bavol, Dmytro; Růžičková, Zdeňka; Pospíšilová, Klára; Fábry, Milan; Král, Vlastimil; Brynda, Jiří; Řezáčová, Pavlína
Abstract: Carbonic anhydrase IX (CAIX) is an enzyme expressed on the surface of cells in hypoxic tumors. It plays a role in regulation of tumor pH and promotes thus tumor cell survival and occurrence of metastases. Here, derivatives of the cobalt bis(dicarbollide)(1‐) anion are reported that are based on substitution at the carbon sites of the polyhedra by two alkylsulfonamide groups differing in the length of the aliphatic connector (from C1 to C4, n =1‐4), which were prepared by cobalt insertion into the 7‐sulfonamidoalkyl‐7, 8‐dicarba‐ nido ‐undecaborate ions. Pure meso‐ and rac ‐diastereoisomeric forms were isolated. The series is complemented with monosubstituted species ( n =2). Synthesis by a direct method furnished similar derivatives ( n =2, 3), which are chlorinated at the B(8, 8') boron sites. All compounds inhibited CAIX with subnanomolar inhibition constants and showed high selectivity for CAIX. The best inhibitory properties were observed for the compound with n = 3 and two substituents present in rac ‐arrangement with K i =20 pM and a selectivity index of 668. X‐ray crystallography was used to study interactions of these compounds with the active site of CAIX on the structural level. Abstract : Co and B combined : Two approaches for synthesis of alkylsulfonamido cobalt bis(dicarbollide) derivatives are described. These compounds serve as highly potent and selective inhibitors of tumor‐associated carbonic anhydrase IX (CAIX). The K i value 20 pM observed for one member of disubstituted family of compounds is the lowest value reported for all boron cluster inhibitors that have been designed and tested to date. Interactions of compounds with the active site of CAIX were explored by X‐ray crystallography.